The crisis of finance-dominated capitalism in the euro area: deficiencies in the economic policy architecture and deflationary stagnation policies - The Levy Economics Institute, Anmandale-on-Hudson; Hein, Eckhard (Anmandale-on-Hudson, NY, 2012)
"In this paper the euro crisis is interpreted as the latest episode in the crisis of finance-dominated capitalism. For 11 initial Euro area countries, the major features of finance-dominated capitalism are analyzed; specifically, the increasing inequality of income distribution and the rising imbalances of current accounts. Against this background, the euro crisis and the economic policy reactions of European governments and institutions are examined. It is shown that deflationary stagnation policies have prevailed since 2010, resulting in massive real GDP losses; some improvement in the price competitiveness of the crisis countries but considerable and persistent current account imbalances; reductions in government deficit-to-GDP ratios but continuously rising trends in gross government debt-to-GDP ratios; a risk of further recession for the euro area as a whole—and the increasing threat of the euro's ultimate collapse. Therefore, an alternative macroeconomic policy approach tackling the basic contradictions of finance-dominated capitalism and the deficiencies of European economic policy institutions and strategies—in particular, the lack of (1) an institution convincingly guaranteeing public debt and (2) a stable and sustainable financing mechanism for acceptable current account imbalances-is outlined."